2018
DOI: 10.3390/nu10091331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Phase Angle in Non-Dialysis CKD Stage 5 and Peritoneal Dialysis Patients

Abstract: Background: Fluid overload and protein-energy wasting (PEW) are common in patients with end-stage renal disease (ESRD) and lead to a poor prognosis. We aimed to evaluate the volume and nutritional status of ESRD patients and to determine the clinical significance of phase angle (PhA). Methods: This study was a cross-sectional comparison of bioimpedance spectroscopy (BIS) findings in patients with non-dialysis chronic kidney disease (CKD) stage 5 (CKD5-ND, N = 80) and age/sex-matched peritoneal dialysis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 33 publications
6
51
0
Order By: Relevance
“…Phase angle has been significantly associated with death in NDD treatment CKD patients [ 34 ]. Despite recognized clinical applicability [ 35 ], phase angle did not present good capacity to diagnose low muscle mass and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Phase angle has been significantly associated with death in NDD treatment CKD patients [ 34 ]. Despite recognized clinical applicability [ 35 ], phase angle did not present good capacity to diagnose low muscle mass and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that PhA was positively associated with a geriatric nutritional risk index, lean tissue index, and albumin level in non-dialytic stage 5 CKD and PD patients. However, there was no association between PhA and Hb level in those patients [ 22 ]. González et al.…”
Section: Discussionmentioning
confidence: 99%
“…In many diseases, the PhA is known to be linked to nutritional status and to predict morbidity and mortality for certain diseases [1][2][3]. The PhA can also reflect the nutritional status of patients with end stage renal disease (ESRD) undergoing maintenance hemodialysis or not on dialysis [5][6][7]. The PhA has been used to study other diseases, but few studies have been conducted exclusively on patients with DMCKD stage 5.…”
Section: Discussionmentioning
confidence: 99%
“…The phase angle (PhA) is known as an indicator of cell integrity and a predictor of body cell mass, and has been suggested to be a prognostic, health, functional, and nutritional indicator of several diseases [1][2][3][4]. Of course, studies on the PhA have also been published in the area of kidney disease [5][6][7]. The PhA is a strictly objective rather than subjective measure.…”
Section: Introductionmentioning
confidence: 99%